Factors Influencing Mental Health Among Chinese Medical and Non-medical Students in the Early Stage of the COVID-19 Pandemic - Xiong, Peng; Ming, Wai-kit; Zhang, Caiyun; Bai, Jian; Luo, Chaohua; Cao, Wenyuan; Zhang, Fan; Tao, Qian (Frontiers in Public Health, 2021)
Background: The 2019 coronavirus disease (COVID-19) pandemic is a public health emergency of international concern. This study aimed to assess the psychological outcomes and their influencing factors among medical and non-medical University students during the COVID-19 pandemic in China. Methods: A cross-sectional online survey using structured questionnaires was conducted from February 20 to March 20, 2020. Psychological outcomes were assessed according to the Depression, Anxiety, and Stress Scale (DASS-21). Influencing factors were assessed by COVID-19 knowledge, mindful coping scale, and sense of control scale. Results: Our sample is comprised of 563 University students (male = 172, mean age = 21.52). Among them, 382 are medical students. Among the participants, 12.26, 18.47, and 8.53% have moderate to severe levels of depression, anxiety, and stress symptoms, respectively. Compared with the non-medical students, the medical students had a higher knowledge level of COVID-19, a higher sense of awareness, and fewer mental health symptoms. After controlling the covariance, perceived constraints of sense of control were negatively associated with depression, anxiety, and stress among both medical and non-medical students. Prevention of negative emotions by mindful coping was negatively associated with depression and anxiety among non-medical students. Knowledge of COVID-19 is not associated with mental distress among medical and non-medical students. Conclusions: During the COVID-19 pandemic in China, the mental health of University students was affected. Our findings suggested that a sense of control is a protective factor for both medical and non-medical students, while mindful coping is a protective factor for only non-medical students.